Improving Student Discipline through Interaction with PAI Teachers in Class 11 of SMK Muhammadiyah 2 Gresik - Lhudin, Ervin Achmad; Amirudin, Noor (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
Educators play a significant role in improving student discipline. Teachers are not the only party that determines the success or failure of students, but their position and role are vital. Therefore, the teacher must successfully form discipline. The approach used is field research using qualitative methods. Qualitative research is a study that aims to describe or analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals or groups of people. By using interview, documentation, and observation methods, the researcher found that the role of teachers in relation to students is influenced by the interactional contexr they face, such as the formal teaching context and in the classroom, so it is clear theat the learning process is different. The interactional between PAI teachers and students has a positive impact on improving student discipline in class XI of SMK Muhammadiyah 2 Gresik